Longitudinal analysis of microfinance borrowers in Brazil: A dynamic market segmentation. (30th May 2021) - de Souza, Lucas Lopes Ferreira; Bassi, Francesca; de Freitas, Ana Augusta Ferreira
Abstract: This study uses a dynamic modelling approach to group clients of a microcredit programme in Brazil and follows them over time. Five segments are identified based on variables related to business, owners, families and operations performed within the programme. Results show that borrowers' circumstances are diverse and different actions are needed for each group. Many customers remained in the same segment; some moved to segments with worse conditions. However, the fact that one fourth of borrowers improved conditions is promising, considering the risky nature of entrepreneurial activity and the Brazilian economic context. Our analyses show that mission drift does not occur.